Application of big data and business analytics - Kumari, Sneha; Tripathy, K. K.; Kumbhar, Vidya (Emerald Publishing Limited, 2020)
Application of Big Data and Business Analytics uses advanced analytic tools to explore the solutions to problems in society, environment and industry. The chapters within bring together researchers, engineers and practitioners, encompassing a wide and diverse set of topics in almost every field.